CIRI-CIRI BAHASA MELAYU PONTIANAK BERBASIS KORPUS LAGU BALEK KAMPONG - Dedy Ari Asfar (Balai Bahasa Kalimantan Barat, 2019)
The aims of this studies is to describe the characteristics of Pontianak Malay language based on the corpus of the Balek Kampong song that popularized by the Arwana music group. The problem of this study is how the Pontianak Malay vowels and consonants, Pontianak Malay diphthongs, pronouns lexicon and kinship system in Pontianak Malay language are based on the corpus of Balek Kampong song. Researcher used descriptive methods to solve the problem and research objectives of this study. The processing and analysis of the Balek Kampong song corpus in this study also used a computerized linguistic Elan and Toolbox. The results of the study prove that there are Pontianak Malay language features, such as the form of schwa vowels /ə/, diphthongs, consonants of fricative velar /ɣ/, and glotal /ʔ/ as typical Malay Malay words in the corpus. In addition, in the Pontianak Malay language corpus studied there were also forms of first person self-name pronouns as well as the Pontianak Malay kinship system lexicon. From the results of this study, it can be concluded that the corpus-based research song can describe the characteristics of the natural speech of Pontianak Malay.